HUBUNGAN BEBAN KERJA DENGAN KINERJA KARYAWAN DI RUMAH SAKIT NUR HIDAYAH BANTUL - Mudayana, Ahmad Ahid (Universitas Ahmad Dahlan, 2012)
Background: The process of development is Nur Hidayah Hospital (RS Nur Hidayah) Bantulmakes employees work load increases. Improved performance the hospital can improveemployee performance. If the employees performance is getting better, the service given to thepatients will be getting better too. The researcher interested to do research the relationship ofworkload with performance of employees.Method: This was descriptive research using cross sectional approach. Research of methodthat used quantitative, the number of 79 employees respondents. The data analyzed usingcorrelation analysis. Workload assessed by questionnaire, performance while using a checklist.Result: Performance (92,4 %) employees are included in the high category, while for themajority of the workload of employees included in the medium category with a percentage 54, 4%. There is no significant relationship of workload with employee performance (p (0,066)>0, 05).Conclusion: This study shows employee performance is already high. There is no significantrelationship of workload with employee performance Nur Hidayah Hospital in Bantul.Key words: Work load, performance